Temperature-induced reversible conformational change in the first 100 residues of α-synuclein - McNulty, Brian C. (Cold Spring Harbor Laboratory Press, 2006)
Natively disordered proteins are a growing class of anomalies to the structure–function paradigm. The natively disordered protein α-synuclein is the primary component of Lewy bodies, the cellular hallmark of Parkinson’s disease. We noticed a dramatic difference in dilute solution (1)H-(15)N Heteronuclear Single Quantum Coherence (HSQC) spectra of wild-type α-synuclein and two disease-related mutants (A30P and A53T), with spectra collected at 35°C showing fewer cross-peaks than spectra acquired at 10°C. Here, we show the change to be the result of a reversible conformational exchange linked to an increase in hydrodynamic radius and secondary structure as the temperature is raised. Combined with analytical ultracentrifugation data showing α-synuclein to be monomeric at both temperatures, we conclude that the poor quality of the (1)H-(15)N HSQC spectra obtained at 35°C is due to conformational fluctuations that occur on the proton chemical shift time scale. Using a truncated variant of α-synuclein, we show the conformational exchange occurs in the first 100 amino acids of the protein. Our data illustrate a key difference between globular and natively disordered proteins. The properties of globular proteins change little with solution conditions until they denature cooperatively, but the properties of natively disordered proteins can vary dramatically with solution conditions.